Michelle Ho Siaw Wei recipient of Chancellors Award makes father source of inspiration - Nurul Ateeqah, Othman (2022)
PAYA BESAR, 5 December 2022 - Michelle Ho Siaw Wei, 24, who hailed from Miri, Sarawak, made her father Ho Sing Huat, 53, who works as a salesperson, a source of inspiration.